Flood protection gap: Evidence for public finances and insurance premiums - Mario Bellia; Francesca Erica Di Girolamo; Andrea Pagano; Marco Petracco Giudici (European Commission, 2023)
Climate-related physical risks pose serious concerns for both public and private finances, and it is of utmost importance to contain economic losses when natural catastrophes occur. In this context, the paper models the potential economic impact of currently uninsured floods in the EU. It also assesses the potential reduction in economic losses by increasing the minimum level of flood insurance penetration, and the resulting increment in total premiums required to achieve this objective. First, the paper estimates the share of premiums associated with insured floods events over total premiums. Then, it investigates the extra premiums needed to close the flood protection gap by requiring all EU countries to reach a minimum level of insurance protection. Third, the paper proposes a stylised approach to quantify economic losses associated with uninsured flood events at different levels of insurance penetration, allowing to take into account that insurance protection could be partly ineffective due to defaults in the insurance sector. The model can be used to assess the size of the potential contingent loss for public finances if no preventive measures are taken to increase society's resilience against climate and weather-related risks, and compare it with a safeguard mechanism under an "average" or "worstcase" scenario. Results show that insurance premiums should be at least doubled to reach a harmonised level of penetration equal to 75%. Results show that average yearly uninsured losses could amount to EUR 27 billion today. Under an alternative scenario accounting for an increase in insurance penetration, losses would decrease by up to 50%.
Keywords: C15; G22; E6; Q54; 330; Physical risk; flood events; insurance; protection gap; insurance premiums